Monomeric Ti(iv)-based complexes incorporating luminescent nitrogen ligands: synthesis, structural characterization, emission spectroscopy and cytotoxic activities. Issue 47 (18th November 2016) - Khalil, Georges; Orvain, Christophe; Fang, Lu; Barloy, Laurent; Chaumont, Alain; Gaiddon, Christian; Henry, Marc; Kyritsakas, Nathalie; Mobian, Pierre
Abstract : Novel photoluminescent 2, 2′-bipyrimidine ligands and their titanium(iv ) complexes are cytotoxic. Abstract : This manuscript describes the synthesis of a series of neutral titanium(iv ) monomeric complexes constructed around a TiO4 N2 core. The two nitrogen atoms that compose the coordination sphere of the metallic center belong to 2, 2′-bipyrimidine ligands homo-disubstituted in the 4 and 4′ positions by methyl (2a ), phenylvinyl (2b ), naphthylvinyl (2c ) or anthrylvinyl (2d ) groups. The crystal structures of these complexes named [Ti(1 )2 (2a )], [Ti(1 )2 (2b )], [Ti(1 )2 (2c )] and [Ti(1 )2 (2d )] (where1 is a 2, 2′-biphenolato ligand substituted in the 6 and 6′ positions by phenyl groups) are reported. The hydrolytic stability of the four complexes is evaluated by monitoring the evolution of the free2a–d signals by 1 H NMR spectroscopy. For the conditions tested (6 mM, DMSO- d 6 /D2 O: 8/1), a rather good stability with t 1/2 ranging from 180 to 300 min is determined for the complexes. In the presence of an acid (DCl), the hydrolysis of [Ti(1 )2 (2a )] is faster than without an acid. The cytotoxic activity against gastric cancer cells of the titanium-based compounds and the free disubstituted 2, 2′-bipyrimidine ligands is tested, showing IC50 ranging from 6.2 ± 1.2 μM to 274 ± 56 μM. The fluorescence studies of the ligands2a–d, and the complexes [Ti(1 )2 (2a–d )] reveal an important fluorescence loss of the ligands2c and2d upon coordination with the Ti(1 )2 fragment. Frontier orbitals obtained by DFT calculations permit us to explain this fluorescence quenching.